Green Colour-based Metaphorical Terms: Translating EU Documents from English into Lithuanian and Italian - Kamandulytė, Aušra (Vertimo studijos, 2019)
The object of this article is metaphorical terms in EU legal discourse. It discusses the concept of a metaphorical term, the usage of such terms in EU legal acts and their role in modern LSP texts, with a focus on their translation. The study analyses metaphorical terms with the lexeme “green” as used in secondary legislation, published between 2016 and 2017, and the motivation of term formation in the source language and translation strategies of rendering these terms into Lithuanian and Italian. The results suggest that in most cases word-for-word translation is used when translating colour-based metaphorical terms, thereby preserving the colour lexeme of the source language in the target language and, thus, the metaphorical character of the term itself. Although the study covers a relatively short period, it confirms the idea that has already been raised in some papers on terminology about an increasing trend of using metaphorical terms in Lithuanian legal texts, even though this is less persistent than in Italian, the language chosen for comparison.
Keywords: terminology; metaphorical terms; colour-based terms; EU legal discourse; translation